Simplify 2(3v+9)-14-6(-5v-4)
2 answers
2 (3v + 9) - 14 - 6 (-5v - 4)
To simplify this expression, first apply the distributive property:
2(3v + 9) - 14 - 6(-5v - 4) = 6v + 18 - 14 + 30v + 24
Next, combine like terms:
= (6v + 30v) + (18 + 24) - 14
= 36v + 42 - 14
= 36v + 28
Therefore, the simplified expression is 36v + 28.
2(3v + 9) - 14 - 6(-5v - 4) = 6v + 18 - 14 + 30v + 24
Next, combine like terms:
= (6v + 30v) + (18 + 24) - 14
= 36v + 42 - 14
= 36v + 28
Therefore, the simplified expression is 36v + 28.